2014
DOI: 10.1530/eje-13-0676
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular and right atrial function and deformation in patients with subclinical hypothyroidism: a two- and three-dimensional echocardiographic study

Abstract: Background: We sought to investigate right ventricular (RV) function and deformation assessed by three-dimensional echocardiography (3DE) and speckle tracking in patients with subclinical hypothyroidism (SHT), and to evaluate the influence of levothyroxine (L-T 4 ) therapy on RV remodeling. Methods: We included 50 untreated women with SHT and 45 healthy control women matched by age. The L-T 4 therapy was prescribed to all SHT patients who were followed 1 year after euthyroid status was achieved. All study part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
4
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 35 publications
(54 reference statements)
3
4
0
4
Order By: Relevance
“…This finding is very important because global RV strain also includes the interventricular septum in addition to the RV free wall. We have reported similar findings regarding RV and RA mechanics in patients with subclinical hypothyroidism 18 …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This finding is very important because global RV strain also includes the interventricular septum in addition to the RV free wall. We have reported similar findings regarding RV and RA mechanics in patients with subclinical hypothyroidism 18 …”
Section: Discussionsupporting
confidence: 81%
“…Impaired RA function contributes to increased RV filling pressure and further worsening of RV diastolic function in patients with subclinical hyperthyroidism. We have already reported similar findings in patients with subclinical hypothyroidism 18 …”
Section: Discussionsupporting
confidence: 80%
“…4,5 Our study group recently published papers about left and right ventricular mechanics in subclinical hypothyroidism (SHT), and we found significant deterioration of myocardial deformation in SHT patients which is improved, but not restored, after a 1-year substitution treatment. 6,7 Although the investigations demonstrated that alterations of left atrial (LA) size, volume or phasic function could indicate the presence and the severity of heart disease, [8][9][10] this topic has been poorly investigated in SHT. On the other hand, LA function and deformation should be deeply investigated due to significant association with the level of left ventricular diastolic dysfunction, 11,12 which is frequently seen in SHT patients.…”
mentioning
confidence: 99%
“…O sistema cardiovascular é muito afetado pelos hormônios tireoidianos, como é visto tanto no hipertireoidismo quanto no hipotireoidismo. 1,2 Os hormônios da tireoide exercem ações diretas e indiretas sobre o sistema cardiovascular, provocando as manifestações clínicas características das doenças tireoidianas. 3 A deficiência de hormônio tireoidiano afeta a contração do músculo cardíaco, 4 ocasionando uma lentificação do relaxamento miocárdico, prejudicando o enchimento ventricular esquerdo.…”
Section: Introductionunclassified
“…6 Há poucos estudos prospectivos sobre a função do ventrículo direito (VD) em portadores de hipotireoidismo, e geralmente apenas em pacientes com hipotireoidismo subclínico ou hipotireoidismo de curta duração. 1,7,10 Pacientes que se encontram com hipotireoidismo subclínico (quando a concentração de TSH se encontra elevada, mas os hormônios tireoidianos estão em concentrações normais), já apresentam uma alteração na estrutura cardíaca. 11 O presente estudo procura entender em que nível a deficiência do hormônio tireoidiano prejudica o coração direito, e se a disfunção ventricular direita pode contribuir para os sintomas cardiorrespiratórios e o prognóstico dos portadores de hipotireoidismo.…”
Section: Introductionunclassified